Achieving global biodiversity goals by 2050 requires urgent and integrated actions - Leadley, P.; Gonzalez, A.; Obura, D.; Krug, Cornelia B.; Londoño Murcia, M.C.; Millette, K.L.; Radulovici, A.; Rankovic, A.; Shannon, L.J.; Archer, E.; Armah, F.A.; Bax, N.; et al. (Elsevier, 2022)
Governments are negotiating actions intended to halt biodiversity loss and put it on a path to recovery by 2050. Here, we show that bending the curve for biodiversity is possible, but only if actions are implemented urgently and in an integrated manner. Connecting these actions to biodiversity outcomes and tracking progress remain a challenge.